Detection and quantification of S-100 protein in ocular tissues and fluids from patients with intraocular melanoma. Issue 11 (November 1988) - Cochran, A J; Holland, G N; Saxton, R E; Damato, B E; Foulds, W R; Herschman, H R; Foos, R Y; Straatsma, B R; Lee, W R
Abstract : S-100 protein is a 21, 000 dalton acidic calcium-binding protein present in ocular melanomas and some normal ocular tissues. Ocular fluids and extracts of ocular tumours were examined by a sensitive radioimmunoassay that could detect less than 5 ng of S-100 protein in minute volumes of fluid. Three ocular melanoma biopsy specimens had S-100 protein at levels between 25 and 1300 ng/ml, comparable to that found in a cutaneous melanoma biopsy specimen (1000 ng/ml). (SI conversion: ng/ml = microgram/l.) Six melanoma culture lines had 1000 to 125, 000 ng/ml. Four lymphoblastoid cultures had less than 2 ng/ml, and three colon carcinoma cultures had 180 ng/ml. Subretinal fluid from 23 melanoma-containing eyes had 10 to 76, 800 ng/ml. Lesser amounts were found in eyes with small, anteriorly located, lightly pigmented tumours. Vitreous from 3 melanoma-containing eyes had 10, 000 to 11, 000 ng/ml. Vitreous obtained from three eyes during tractional retinal detachment repair had 500 to 1600 ng/ml, and vitreous obtained at necropsy from six normal eyes had 2 to 120 ng/ml. Aqueous from six melanoma-containing eyes had 10 to 30 ng/ml, levels not significantly different from those observed in three normal eyes (80-120 ng/ml). This approach provides new insight into the interaction of ocular tumours and adjacent ocular fluids and may, with more specific tumour markers, have diagnostic applications.